THE IMPORTANCE OF DIGITAL MARKETING IN COMPANIES AS A VITAL TOOL - Pamela Sánchez Brizuela, Evelin; Melissa Zarate, Jenifer; Mikaela Díaz Giménez, Nataly; Manuel Medina Ramírez, Adrian (Revista Gênero e Interdisciplinaridade, 2023)
Digital marketing (or online marketing) are all the actions and strategies that use the internet, digital devices and online platforms to promote, sell or communicate everything related to products or services, customer service and performance monitoring. . This research focuses on analyzing the importance of it in companies as a vital tool, detailing fundamental strategies to achieve proposed goals.The methodology used in the research is Quantitative, data collection was carried out through a survey with semi-open questions.The results indicate that Digital Marketing is extremely important for companies, as well as being a useful tool for them, but the familiarity of the respondents with this system is quite regular.Effective strategies such as television and radio advertising were identified to increase the customer base and improve the profitability of a company. Likewise, effective traditional marketing strategies such as social networks and influence marketing are mentioned, since social networks play a fundamental role in the digital marketing strategy within companies.As a result of the research, useful tips are proposed to implement within companies and promote digital marketing in companies. These include the use of social media and transparent client communication